Study on 3D Scene Reconstruction in Robot Navigation using Stereo Vision - Nurnajmin Qasrina, Ann; Achmad, M. S. Hendriyawan; Bayuaji, Luhur; Mohd Razali, Daud; Pebrianti, Dwi (IEEE, 2016)
In this paper, a 3D scene reconstruction by using stereo vision is presented. Stereo camera parameters from the camera calibration process and disparity map are two important parameters to obtain an accurate result for the 3D reconstruction. 3D reconstruction process generates the coordinates of world points (point cloud). From the information of the point cloud, the interested object is segmented out. Additionally, the noises left in the image is eliminated. The experimental result obtained shows that only the background and the interested object from the overall scene appeared in the processed image. The center of gravity is also determined as the reference value for the robot navigation. An estimation error model is also introduced in this study to increase the accuracy of the distance measurement by using the developed stereo vision system from the mobile robot. This experiment provides a foundation for navigation and object tracking for a mobile robot.